Learning orientation and market information processing: effects on marketing and organizational outcomes - Çaloğlu, Hale. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2016., 2016)
This study proposes a theoretical model, which relates learning orientation directly and also indirectly through market information processing and marketing effectiveness to organizational performance. A second study model, which explicitly recognizes the differential effects across these measures, is also developed. The significance of this study stems from its integrative approach to fragmented streams of literature, which analyze the links between learning orientation, market information processing, marketing effectiveness, new product success and financial performance. The two theoretical models are tested with data collected from 114 companies through structured questionnaires. The findings suggest three significant routes between learning orientation and financial performance. The first route indicates that learning orientation helps the firms to successfully process market information, effectively implement marketing activities for new market - driven product offerings, and thus achieve superior financial performance. The second significant route implies that a learning oriented firm can successfully introduce new market-driving products and achieve subsequent financial success without focusing on its markets. Finally, the third significant route hints that learning oriented firms do not only attain superior financial performance by introducing new products, but also by focusing on their current markets and effectively marketing their current product offerings.
Keywords: Organizational learning.